Hukum Perdata Islam dan Hukum Perdata Indonesia: Penelitian - Nazmi Septrina; Asasriwarni Asasriwarni; Ikhwan Ikhwan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Civil law is a branch of law that regulates relationships between individuals in social life. In the Indonesian context, civil law has two main systems that operate side by side: Indonesian civil law, which originates from the Dutch Civil Code (Burgerlijk Wetboek) and national regulations, and Islamic civil law, which originates from the Qur'an, Hadith, ijma', qiyas, and the Compilation of Islamic Law (KHI). Indonesian civil law emphasizes legal certainty, codification, and the principle of secularity, while Islamic civil law prioritizes justice, welfare, and sharia values. Both cover family, marriage, inheritance, and property, but their regulatory mechanisms differ. District Courts are authorized to handle Indonesian civil law cases, while Religious Courts have jurisdiction over Islamic civil cases for Muslims. Thus, this comparison demonstrates that the two legal systems complement each other in legal practice in Indonesia, reflecting the distinctive legal pluralism and providing alternative dispute resolutions tailored to the needs of society.